INVESTIGATION OF ENVIRONMENTAL COMPLIANCE PERFORMANCE OF COLOURED CONCRETES PRODUCED FROM WASTE RED MUD - Kilic, Yasemin; Gunay, Esin; Marsoglu, Muzeyyen (YILDIZ TECHNICAL UNIV, 2013)
Red mud is a waste generated by the Bayer process and its disposal is a major problem. Waste red mud from Eti Seydisehir Aluminium Plant of Turkey was considered as a hazardous waste for the environment and human health. The storage of the red mud is difficult due to its high amount of various metal oxides, elements and caustic content. In this study, the environmental compliance tests were done and evaluated according to the Regulation on Regularly Storage of Waste of the produced city furnitures with red mud. According to the test results; red mud, a hazardous waste alone, can be used in the city furniture production. The city furnitures produced with red mud does not contain hazardous substances. Also, these city furnitures can be stored as safe substances with Regulation on Regularly Storage of Waste in Turkey. City furnitures produced with red mud preserving colouring properties at +40 degrees C/-10 degrees C for 1 year period.
Keywords: Concrete; environmental compliance test; red mud; life performance test; pigment; Engineering